Democracia participativa e o papel do Ministério Público no controle da atividade política - Sampaio, Anny Gresielly Sales Grangeiro (2015)
This paper aims at analyzing participatory democracy under the citizens' control perspective on political activity, either directly or through prosecutors, addressing the relevance of direct and indirect social control of finances and public policies in order to enhance democracy. It is analyzed the existing mechanisms of participatory democracy and its amplitude, besides the representation crisis and its influence on demands growth, having the judicial review of public policies as an objective, as well as the Judiciary power illegitimacy to analyze politic discussions. From the perspective of participatory democracy, it was discussed social control mechanisms of political activity available to citizens, even as the role of prosecutors in this activity control. The inductive method was applied, with the use of specific assumptions in order to draw general conclusions. The monographic technique was adopted, using bibliographic and documentary research, as tools for findings to be provided by research. Extensive literature research was made, in classical and modern, national and foreign doctrine related to Democracy, Political Science and Constitutional Law, emphasizing the approach on participatory democracy and political activity control. In addition, it was performed documental research by collecting specific data on specialized pages on the World Wide Web, as well as journals and law magazines that addressed the subject matter, making also a comparison with the factual reality of popular participation in the control of political activity by Public Ministry. It was found that political activity control is strengthened and optimized through interventions of the prosecution, which is equipped within instruments and mechanisms of citizenship enforcement and accountability of political representatives.